High-level segment : beyond the curve : UNCTAD and new patterns of growth for trade and development (UN New YorkUS, 2013)
Calls for policymakers in the developed countries to search for policy alternatives to end the expected protracted period of slow growth by re- regulating international finance and stemming the encroachment of multilateral disciplines and bilateral trade and investment agreements on developing countries' policy space at the international level. At the national level , adopting appropriate macroeconomic policies, along with industry policy and active labour market policies to help strengthen the employment content of growth and increase the wage share, thereby boosting inclusive growth.
Keywords: ECONOMIC GROWTH